Enabling Taguchi method with grey relational analysis to optimize the parameters of TiO2/ZnO heat transfer nanofluid for heat pipe application. (11th March 2021) - B, Jacob Rubasingh; Selvakumar, P
Abstract: Our previous work demonstrated that the TiO2 /ZnO (1:1) nanocomposite suspended in ethylene glycol with CTAB (0.5 ml) as surfactant exhibits better heat transfer property than TiO2 and ZnO nanofluid. As an extension, the influence of parameters such as wt.% of ZnO Nps in TiO2 /ZnO nanocomposite (0 wt.%, 25 wt.%, 50 wt.%, and 100 wt.%), the quantity of CTAB (250 μ l, 500 μ l, 750 μ l, and 1000 μ l) and vol.% of TiO2 /ZnO nanocomposite (1 vol.%, 2 vol.%, 4 vol.%, and 8 vol.%) are analyzed through Taguchi design constructed with L16 orthogonal array is emphasized in the present work. As per the Taguchi design, the responses such as viscosity, thermal conductivity, and normalized height % for the set of input parameters are evaluated. Besides, the multiple responses are graded employing Grey relational analysis and the optimum set of parameters to achieve the preparation of the best nanofluid is identified as 25 wt.% ZnO, 1 vol.% nanocomposite and 500 μ l CTAB which display viscosity of 0.043 Pa.s, thermal conductivity of 0.35 Wm −1 K −1, and normalized height % as 1%. Further, the optimal TiO2 /ZnO nanofluid is used as working fluid in heat pipe and compared its results with ethylene glycol. From the calculated thermal resistance and heat transfer coefficient values, the TiO2 /ZnO nanofluid outperforms the base fluid in a significant manner.